POVERTY ALLEVIATION MOVEMENT IN INDONESIA (A COMMUNITY CULTURAL DEVELOPMENT APPROACH) - Safri Miradj (Archipelago, 2020)
The Poverty Alleviation Movement is a movement that uses a cultural approach as a tool to reduce poverty in Indonesia. Because at this time, there have been many strategic steps taken by the government to reduce poverty, the results have not been satisfactory for the poor. So that we need a new framework in solving the problem of poverty. Dibwahini offered several strategic steps in carrying out the poverty alleviation movement. Local cultural traditions are part of instilling a sense of community justice, and helping to give a sense of identity to the community. Development of community culture as a poverty alleviation movement with the following approaches: (Developing community culture, preserving indigenous culture as a community building strength, building indigenous communities, personal development, balanced development, and the role of education in poverty alleviation) This approach should be used as a basis and strength in carry out a poverty alleviation movement. In order for cultural development to be effective in the context of community development, cultural heritage cannot be separated, but must be seen as a real movement in people's lives. And this is a concept that has a very important role in liberating society from the shackles of poverty and ignorance that are experienced by Indonesian society today. Keywords: movement, poverty alleviation